2022
DOI: 10.1159/000523803
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Cellulitis following COVID-19 Vaccination

Abstract: A 72-year-old male patient was referred to our outpatient clinic with a painful left eye protrusion accompanied by marked conjunctival chemosis and external ophthalmoplegia being progressed despite topical and oral antibiotic therapy. He developed ocular symptoms 9 days after receiving his second SARS-CoV-2 vaccine (VeroCell). Of note, in previous history, 2 weeks after the first dose of the COVID-19 vaccine, he also developed a life-threatening laryngeal oedema treated at an emergency care unit. MRI of the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…The orbital signs resolved rapidly with systemic steroids administered under antibiotic cover. There was no evidence of sinusitis in this case unlike the published reports of orbital cellulitis after COVID-19 168 . Delayed development of orbital symptoms (>1 wk and complete resolution with steroids point towards a hypersensitivity reaction to SARS-CoV-2 vaccine) 168 .…”
Section: Orbital Adverse Reactions To Coronavirus Disease 2019 Vaccin...mentioning
confidence: 50%
See 3 more Smart Citations
“…The orbital signs resolved rapidly with systemic steroids administered under antibiotic cover. There was no evidence of sinusitis in this case unlike the published reports of orbital cellulitis after COVID-19 168 . Delayed development of orbital symptoms (>1 wk and complete resolution with steroids point towards a hypersensitivity reaction to SARS-CoV-2 vaccine) 168 .…”
Section: Orbital Adverse Reactions To Coronavirus Disease 2019 Vaccin...mentioning
confidence: 50%
“…Hári-Kovács et al 168 reported a case of unilateral orbital cellulitis without sinusitis developing in a 72-year-old man with diabetes and hypertension 9 days after the second dose of the CoronaVac vaccine. The orbital signs resolved rapidly with systemic steroids administered under antibiotic cover.…”
Section: Orbital Adverse Reactions To Coronavirus Disease 2019 Vaccin...mentioning
confidence: 99%
See 2 more Smart Citations